How to be a Brilliant English Teacher. - Wright, Trevor (Taylor and Francis, 2012)
Now in its second edition, Trevor Wright's hugely popular How to be a Brilliant English Teacher is packed with practical advice drawn from his extensive and successful experience as an English teacher, examiner and teacher trainer. This accessible and readable guide offers sound theoretical principles with exciting practical suggestions for the classroom. Fully updated to include a new expanded section on differentiation and inclusion, as well as covering new material on behaviour management and teaching poetry for enjoyment and personal response, this book tackles ot.